UNUSUAL RIBOSOME PARTICLES OCCURRING DURING SPORE GERMINATION - Woese, Carl R. (1961)
Woese, Carl R. (Yale University, New Haven, Conn.). Unusual ribosome particles occurring during spore germination. J. Bacteriol. 82:695–701. 1961.—Spores of Bacillus subtilis germinated for varying amounts of time were disrupted under conditions of varying divalent ion concentration and analyzed for content of ribosomes by ultracentrifugal techniques. The picture of microsome development during germination is as follows: The spore contains only 50S and 68S particles. Early in germination, 25S and 35-8S particles increase in amount first. These particles seem to be formed in close association with the cell deoxyribonucleic acid. Their binding in the cell requires a chelating agent to release them maximally. Further, 25S and 35-8S particles are the only ones sensitive to ribonuclease and the only ones produced in the presence of chloramphenicol. The kinetics of their appearance, and their relative size, suggest them as precursors of 50S particles, which increase in amount shortly after appearance of 25S and 35S particles. It was found that 31S particles do not appear until later in germination, and their appearance signals a rise in 68S material, suggesting again the oft-reported relationship: one 31S + one 50S = one 68S. We have been unable to discern any precursors of the 31S material in these studies.